Edukasi Pengelolaan Uang Halal bagi Generasi Alpha Untuk Meningkatkan Literasi Keuangan Syariah - Iis Maulidiyah (JPPMI: Jurnal Pelayanan dan Pemberdayaan Masyarakat Indonesia, 2026)
The low level of Islamic financial literacy among the younger generation has become the basis for implementing this community service program. The activity aims to improve the understanding of Generation Alpha regarding halal financial management from an early age. The method used is Participatory Action Research (PAR), which actively involves participants in the stages of planning, implementation, and evaluation. The program was conducted at Ayo Cerdas Indonesia Institute with a total of 25 participants aged 7–12 years. Data collection was carried out through observation of participants' level of participation and understanding during the activities. The results indicate an increase in participants' understanding by approximately 70%, as reflected in their ability to answer questions and engage in discussions after the program. Participants also began to understand the basic concepts of Islamic financial literacy, such as the importance of saving, managing expenses, and avoiding riba (usury). The interactive approach through discussions and educational activities proved effective in enhancing financial awareness and shaping more responsible economic behavior from an early age. Therefore, this program has a positive impact on improving Islamic financial literacy among Generation Alpha and should be implemented sustainably